PENGGUNAAN METODE SQ3R TERHADAP HASIL BELAJAR AKUNTANSI SISWA - Rixaza Rixa Rixala Harahap, Rijal Lubis (FKIP UMN ALWASHLIYAH, 2020)
Learning method is the method used to implement a plan that has been prepared in the form of real and practical activities in order to achieve the learning mission, which is a method chosen by educators to be able to optimize the teaching and learning process that aims so that learning objectives can be expected. Cooperative learning method type SQ3R is a learning method that uses reading strategies by assigning students to read study material carefully. This inspires the writer to apply the SQ3R learning method so that students are required to play an active role, so students will more easily understand the subject matter delivered by the teacher. The formulation of the problem in this study is